A case study of Compulsive Buying Disorder (CBD) among online shoppers in Malaysia / Muhammad Fauzan Othman, Nur Amera Abdul Hamid and Wan Aina Aqilah Mohd Khari - Othman, Muhammad Fauzan; Abdul Hamid, Nur Amera; Mohd Khari, Wan Aina Aqilah (2019)
In this cyber era, internet is the most important thing to have in order to do a bank transaction, working, learning or shopping. All of this activities can be done online. Online shopping also now becoming the common compared to traditional shopping pattern. This trend cause from the rapidly enhancing in the world of technology. This shopping pattern be more convenient to people because it easy to communicate and dealing with the business. Based on the previous research, online shopping trend phenomenon also happen in Malaysia. It confirmed by the previous research that Malaysia state in top ten market that have the higher number of online shoppers. This trend striking upward because the rise of Malaysia economy and lead of Malaysian to have a high income. Because of this the lifestyle of Malaysian is in a high rate. This give potential to the Malaysian to have a Compulsive Buying Disorder (CBD) addiction Compulsive Buying Disorder (CBD) is an uncontrollable of spending habit that can lead to the negative impact. So, the Primary aim of this study is to determine the CBD person in Malaysia and the common characteristic background of a person who has CBD in Malaysia. This study also want to know the factor that contribute this disorder in Malaysia. A questionnaire survey was designed and conducted. This questionnaire had been distributed through online platform such as WhatsApp, Twitter, Facebook and many more order to get the information. This questionnaire be blast online because it suitable with the topic with is online shopping. The data information was collected within the semester break from January to February 2019. This questionnaire carried out the data from 390 respondents around Malaysia who willingness to participants in this study.On the data analysis, the method use are descriptive analysis to analyse the demographic background, factor analysis in order to get the common factor that contributing to the CBD. Lastly using Logistic analysis since the output is binary, there are two output for this research which are CBD addiction or not. So logistic model seen to be most appropriate to be used in this study. The result shows that there are 95 people from 390 respondent who have CBD addiction. The background is lead to female who range between 21 to 30 years old, a degree holder and having an income between RMI to RMI 000. For the factor, there are three factor that lead to the CBD in Malaysia which are Excessive internet usage, depression and relationship problem. For the logistic model, all the three factor are significant to the model.